Drug eluting electrospun scaffolds for tissue regeneration - Van den Bergh, Willem Johannes Wian (Division of Biomedical Engineering, 2019)
The desired healing response to electrospun scaffolds in tissue engineering is often limited by poor ingrowth due to insufficient porosity, thrombogenicity, lack of vascularisation and/or excessive inflammation. This study aimed at increasing structural porosity and incorporating/delivering anti-thrombotic/angiogenic (heparin) and anti-inflammatory (dexamethasone) agents. Porosity enhancement techniques were explored using two different approaches i) electrospinning of biostable polymer (Pellethane® , Pel) with concomitant electrospraying of soluble microparticles, which were subsequently removed to increase scaffold interconnectivity and ii) electrospinning of biodegradable polymer (DegraPol® , DP) at low collecting temperatures. Dexamethasone (Dex) was incorporated by simple admixture, while heparin (Hep) required chemical modification (heparin tributylammonium, HepTBA) to achieve solubility. Release rates were determined in vitro, followed by thrombogenicity (thromboelastography) and cytotoxicity (cell viability) assessments of modified/unmodified heparin prior to incorporation and after elution. Finally, in vivo responses were evaluated in a subcutaneous model (24 rats) for up to 12 weeks. Porosity was enhanced (P0.1). At 12 weeks of implantation, high-porosity Pel scaffolds allowed for full tissue ingrowth (>98%) while conventional scaffolds were limited (0.3). High-porosity scaffolds produced by combined electrospinning/spraying have the potential to enhance healing. Dex or HepTBA can be incorporated and eluted from degradable electrospun scaffolds, and localised delivery of HepTBA improves implant vascularisation. This study may contribute towards tissue engineered vascular graft development where anti-thrombogenicity and increased vascularisation are desired.